Konsep Keluarga Harmonis dalam Konteks Hukum Islam - Samsul Arifin; Khairuddin (UNIVERSITAS BONDOWOSO, 2023)
Marriage is human nature as the fulfillment of the demands of human instincts cannot be denied. Besides that, marriage is also part of the sunnah of the Prophet Muhammad SAW which has a basis in the Koran and al-Sunnah. One of the verses of the Koran that talks about marriage is surah ar-Rum 30:21. In this verse it is explained that building a household through legal marriage aims to create peace, tranquility and happiness in this world and the hereafter. Based on this explanation, this paper aims to describe household harmony in the Islamic view. While the method used in this research is to use library research instruments, namely research by examining scientific books, researching books that have relevance to the object of research, articles, books written by scholars, the internet and others, as supporting factors that underlie theoretical basis. The results of this study indicate that in general building family harmony can be achieved through two aspects. The first is the spiritual aspect related to Hablumminallah (Vertical Relations) and the second is the material aspect which is related to issues that are more technical in nature, for example husband and wife can share roles in managing the household.